Black feminism in qualitative inquiry : a mosaic for writing our daughter's body - Evans-Winters, Venus E. (Abingdon, Oxon ; New York, NY : Routledge, 2019)
Recently, Black women have taken the world stage in national politics, popular culture, professional sports, and bringing attention to racial injustice in policing and the judicial system. However, rarely are Black women acknowledged and highlighted for their efforts to understand the social problems confronting our generation and those generations that came before us. In the post-civil rights era, research faculty and theoreticians must acknowledge the marginalization of Black women scholars' voices in contemporary qualitative scholarship and debates. Black Feminism in Qualitative Inquiry: A Mosaic for Writing our Daughter's Body engages qualitative inquiry to center the issues and concerns of Black women as researcher(s) and the researched while simultaneously questioning the ostensible innocence of qualitative inquiry, including methods of data collection, processes of data analysis, and representations of human experiences and identities. The text centers "daughtering" as the onto-epistemological tool for approaches to Black feminist and critical race data analysis in qualitative inquiry. Advanced and novice researchers interested in decolonizing methodologies and liberatory tools of analysis will find the text useful for cultural, education, political, and racial critiques that center the intersectional identities and interpretations of Black women and girls and other people of color. Daughtering as a tool of analysis in Black feminist qualitative inquiry is our own cultural and spiritual way of being, doing, and performing decolonizing work.
OCLC-licensed vendor bibliographic record.
Keywords: Feminism -- Research -- United States; Women, Black -- United States; African American women; African American feminists; Racism -- United States; Qualitative research; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; SOCIAL SCIENCE / Research